2015
DOI: 10.1111/and.12436
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of thymoquinone on experimental testicular ischaemia-reperfusion injury: an apoptotic, proliferative and biochemical study

Abstract: The objective of this study was to examine the effects of thymoquinone (TQ), which has antioxidant properties in the experimental testicular I/R model in rats in terms of its anti-apoptotic, proliferative and biochemical attributes. In our study, 24 male rats were divided into three groups: control group, I/R group and I/R+TQ group. Testicular torsion was created by rotating the left testis 720° in a clockwise direction. The ischaemia period was 4 h, and an orchiectomy was performed after 4 h of detorsion. Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…For histopathological examination, MTBS method was utilised for the evaluation of seminiferous injuries and MSTD was performed for measuring the seminiferous tubules diameter, both of which were frequently used in testicular damage models for histopathological examinations (Erboga et al., ; Kanter, Aktas, & Erboga, ). In our study, both MTBS and MSTD values were decreased in ethanol group.…”
Section: Discussionmentioning
confidence: 99%
“…For histopathological examination, MTBS method was utilised for the evaluation of seminiferous injuries and MSTD was performed for measuring the seminiferous tubules diameter, both of which were frequently used in testicular damage models for histopathological examinations (Erboga et al., ; Kanter, Aktas, & Erboga, ). In our study, both MTBS and MSTD values were decreased in ethanol group.…”
Section: Discussionmentioning
confidence: 99%
“…The favourable effect on the sperm parameters was due to the excellent ability of N. sativa to inactivate free radicals and prevent oxidative stress in the semen of infertile subjects (Kolahdooz et al, 2014). To support this assumption, thymoquinone, the major pharmacologically active component of N. sativa oil was also tested in different animal models and was found to re-establish spermatogenesis and protect against testicular ischaemia-reperfusion injury and chemically induced testicular injury through an antioxidant mechanism (Erboga et al, 2016;Kanter, 2011;Salahshoor, Haghjoo, Roshankhah, Makalani, & Jalili, 2018). Apparently, there are yet no clinical trials conducted in infertile men treated with thymoquinone except the only one study that evaluated the effects of N. sativa oil in childless men (Kolahdooz et al, 2014).…”
Section: Ni G Ell a Sativamentioning
confidence: 99%
“…catalase (CAT), glutathione peroxidase (Gpx), superoxide dismutase (SOD), and nitrite nitrate (NIT)] and decreasing lipid peroxidation (Kanter et al ., ; Awad et al ., ). Over the last decade, studies of I/R injury have reported that TQ reverses the toxic effects ROS in the affected organ (Bayrak et al ., ; Erboga et al ., ).…”
Section: Introductionmentioning
confidence: 97%